Peningkatan Mutu Hasil Belajar Siswa Kelas IX.A SMPN 7 Pujut pada Materi Sistem Ekskresi Melalui Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions - Wirejati Wirejati (Universitas Pendidikan Mandalika, 2019)
This research aims to improve student learning outcomes through STAD type cooperative learning. This research method uses classroom action research. The subjects of this study were 35 students of grade IX.A of SMP Negeri 7 Pujut. This research took place in 2 cycles. Data analysis techniques using quantitative and qualitative descriptive analysis. The results of this study indicate that an increase in student learning outcomes by 86.9%. This is supported by the results of student and teacher observations that show an increase in both categories. The results of this study conclude that by using the STAD type cooperative learning model can improve student learning outcomes in the excretion system material.